The effect of Proprioceptive Neuromuscular Facilitation on Quality of Life of patient with stroke - Avazpour, Mohsen; Solaiman, Afroughi; Amin, Haghgoo; Fatemeh, Martoob; Yaghoub, Parandvar (International Journal of Psychosocial Rehabilitation, 2020)
Regarding the importance of nursing and rehabilitation measures on reduction of complications in patients with stroke, the present study was done to examine the effect of Proprioceptive Neuromuscular Facilitation (PNF) exercise on Quality of Life (QOL) in stroke patients. This clinical trial study was performed on 60 patients with stroke referred to martyr Beheshti Hospital of Yasuj in 2018, Iran, Which lasted 4 months to 2 years from their illness. These patients were selected by random sampling, then assigned to two groups of 30 as control and intervention. The data collection tool was a shortened World Health Organization Quality of Life (WHO. QOL. Brief) Questionnaire. At first, quality of life was measured in both groups. Then, the intervention group received Proprioceptive Neuromuscular Facilitation exercise for 8 weeks. Immediately and 4 weeks after the last session of the exercise, the quality of life of the patients was measured. Then, the collected data were analyzed using Kolmogorov-Smirnov statistical tests, repeated measure ANOVA and Post-Hoc and SPSS software.The findings of this study showed that there was no significant difference in the parameters of quality of life in stroke patients before the intervention between the two groups (P>0.05), but immediately and one month after the intervention, a significant statistical difference was reported between the two groups based on Repeated Measurement Anova Test (P <0.05). According to the findings of this study, it can be concluded that Proprioceptive Neuromuscular Facilitation exercise has been able to improve the quality of life of patients with cerebrovascular accident